A preliminary assessment of the Permian and Triassic insect records from southern South America - Lara, Maria Belén (2021)
During the late Paleozoic-early Mesozoic, southwestern Gondwana comprised extensive areas that are nowadays represented in southern South America throughout significant continental deposits bearing abundant and diverse invertebrate fossils. The insect record is however, mostly known from Argentina, being less common in Brazil, Chile and Uruguay, probably due to poor exploration and lack of identification of deposits with insect fossils. Currently, there are a total of 37 fossil insect species described from Permian units in South America, in which only forewing impressions are preserved. For the Triassic, the entomological picture is completely different; approximately 97 species have been identified to date, based on more than a thousand specimens (mainly forewings and isolated elytra) collected from different outcrops. A thorough compilation of the literature, together with the addition of abundant, new fossil insect material collected after several fieldwork seasons by this research group, indicates that the entomofaunas recorded in South America are consistent with the proposal of a ?Paleozoic Evolutionary Fauna? shifting to a ?Modern Evolutionary Fauna? after the Permo?Triassic mass extinction event. This transition is reflected in the South American faunas by the turnover of the Paleozoic basal clades (e.g., archaeorthopterans, megasecopterans, diaphanopterodeans, palaeodictyopterans, ?protorthopterans?, protophasmids, blattodeans, hemipteroids, among others), by more modern and derived taxa in the Triassic (e.g., dipterans, hymenopterans, odonatans, scorpionflies, aquatic heteropterans, etc.). Despite this apparent faunistic replacement, some Permian insect groups crossed the P/T limit and remained well into the Triassic (e.g., Scytinopteridae, Dysmorphoptilidae), further supporting a gradual turnover between these two entomofaunas. The entomological differences observed in the numerous Permian and Triassic units considered in this preliminary study, could be related to floristic, environmental, and climatic changes, as this time interval is crossed by salient events of both local and regional extent, such as extreme temperature fluctuations, intense magmatism and the major extinction event ever recorded. Nonetheless, collection and taphonomic biases should not be ruled out, as paleoentomology is rarely considered as a line of investigation in South American countries, resulting in lack of exploration and delayed knowledge of past invertebrate faunas.